2017
DOI: 10.1186/s12974-017-0878-6
|View full text |Cite
|
Sign up to set email alerts
|

Thioredoxin-interacting protein links endoplasmic reticulum stress to inflammatory brain injury and apoptosis after subarachnoid haemorrhage

Abstract: BackgroundEarly brain injury (EBI) is considered a major contributor to the high morbidity and mortality associated with subarachnoid haemorrhage (SAH). Both of sterile inflammation and apoptosis are considered the important causes of EBI. Recently, it was confirmed that thioredoxin-interacting protein (TXNIP) not only participates in inflammatory amplification but also stimulates the apoptosis signalling cascade pathway. However, whether the effects of TXNIP influence the pathogenesis of SAH remains unclear. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
44
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 52 publications
4
44
0
Order By: Relevance
“…In different disease models, MCC950 has provided conspicuous protection either in CNS disease models (i.e., Alzheimer's disease [AD] 27 or systemic disorders like diabetic vascular dysfunction). [28][29][30][31] Here, we specified that MCC950 could also alleviate TBI and the consequent proinflammatory and, in particular, proapoptotic signals in the perilesional area.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In different disease models, MCC950 has provided conspicuous protection either in CNS disease models (i.e., Alzheimer's disease [AD] 27 or systemic disorders like diabetic vascular dysfunction). [28][29][30][31] Here, we specified that MCC950 could also alleviate TBI and the consequent proinflammatory and, in particular, proapoptotic signals in the perilesional area.…”
Section: Discussionmentioning
confidence: 99%
“…Extensively studied for its contribution to insulin resistance and oxidative stress, TXNIP directly associates with NLRP3 and induces inflammasome oligomerization and activation and modulates the expression of various cytokines and proapoptotic signals. 25,29,45,46 TXNIP has been also found be upregulated in response to brain injury coincident with inflammasome activation. 47 Presumptively, this takes place downstream to reactive oxygen species (ROS) release, which, in turn, promotes TXNIP expression trough transcription factor forkhead box O3 (FoxO) in TBI brains.…”
Section: Discussionmentioning
confidence: 99%
“…Aneurysmal subarachnoid hemorrhage (SAH) is a devastating cerebrovascular disease with a high rate of mortality and disability [ 1 ]. Neuroinflammation and blood-brain barrier (BBB) disruption have been recognized as important pathological processes in early brain injury (EBI) after SAH [ 2 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, several recent studies have demonstrated that TXNIP mediates neuron apoptosis and inflammation during post-SAH EBI, while ER-stress-induced suppression in TXNIP expression could lead to reduced expression of some prognostic indicators and inhibited cell apoptosis and inflammation. Therefore, it was suggested that the suppression of TXNIP may become a potential therapeutic strategy for the treatment of SAH [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, melatonin has been reported to protect the brain against post-SAH injury [ 17 ]. For example, it was found that the administration of melatonin could regulate the nuclear factor erythroid-2 related factor 2 (Nrf2) signaling pathway to reduce ER stress, which is considered a key contributor to post-SAH EBI [ 12 , 18 20 ]. In this study, we established an animal model of SAH and subsequently gave melatonin treatment to SAH animals.…”
Section: Introductionmentioning
confidence: 99%